Roma teaching assistants in primary schools - Bačlija Brajnik, Irena (Teorija in praksa, 2019)
One of the many measures used to improve the integration of Roma into national education systems is regarded as particularly successful: Roma teaching assistants. Although Roma teaching assistants are internationally promoted and recommended, some Roma representatives remain cautious about their use as their effectiveness may be questioned and their subordination to teachers may ultimately keep marginalised pupils in subservient positions. Based on empirical research, this article finds the mechanism of Roma teaching assistants in Slovenia is well implemented, yet such assistants are in a subordinate position to teachers and along with Roma pupils often physically separated from the rest of the class. However, they maintain a very friendly relationship with both teachers and pupils and principally act as a cultural and linguistic bridge.
Keywords: Elementary school; Instructional systems; integracija; Izobraževalni sistemi; Osnovna šola; Romanies; Romi; romski pomočniki; segregacija; učno osebje